2017
DOI: 10.9790/3013-070201111116
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a LC-UV Method Applied to the Quality Control of Ursodeoxycholic Acid in Raw Material and Pharmaceutical Formulations

Abstract: Abstract:-A simple, fast, and sensitive HPLC method with UV detection has been developed for the quantitation of ursodeoxycholic acid (UDCA) in raw material and pharmaceutical formulation (suspension). Cromatographic conditions were: Symmetry-C18 column (150 mm x 4.6 mm, id; particle size 5 µm), 40 ˚C, 100 µL injection volume and UV detection at 200 nm. The flow rate was 1 ml/min using acetonitrile -phosphoric acid (pH 3.0; 0.15mM) (48:52) as mobile phase. The method was validated according to international gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…23 The linearity results obtained the correlation coefficient (R) for the assay and dissolution test of 1 and 0.9995, respectively. The linearity results in this study show in a fairly good R value than previous studies for assay that resulted (R) 0.9951 24 , and (R) 0.9998 25 . Whereas for the dissolution test from previous study the (R) value was (R) 0.9990.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…23 The linearity results obtained the correlation coefficient (R) for the assay and dissolution test of 1 and 0.9995, respectively. The linearity results in this study show in a fairly good R value than previous studies for assay that resulted (R) 0.9951 24 , and (R) 0.9998 25 . Whereas for the dissolution test from previous study the (R) value was (R) 0.9990.…”
Section: Discussionsupporting
confidence: 54%
“…From the LOD and LOQ values in present study, this method still satisfy for quantification of Ursodeoxycholic acid in formulation because from previous research the usual concentration of Ursodoxycholic acid from sample formulation in the test solution in between 200-15000 µg/mL. 7,9,10,11,14,23,24,25,26,27 From the results assay of Ursodeoxycholic acid capsule samples, it was obtained the average concentration of 6 capsules was 103.50±1.47% and Ursodeoxycholic acid dissolved was 97.61±3.97%. This value meets the requirements set by the USP 42 nd for assay between 90-110% and dissolution test ≥ 80%…”
Section: Discussionmentioning
confidence: 64%
“…UDCA concentration was determined by HPLC-UV [ 41 ]. HPLC was equipped with a reverse phase C18 column—Waters Symmetry (150 mm × 4.6 mm, id; 5 μm particle size).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it met the USP specification for dissolution testing. The UDCA content was determined by HPLC-UV according to a previous work [41]. In this sense, the official USP UDCA monograph describes a liquid chromatography (LC) method coupled to a differential refractive index detector due to the low absorptivity of bile acids.…”
Section: Dissolution Testmentioning
confidence: 99%
“…To determine the assay of the drug during the storage period, stability indicating analytical method play an important role. There are few analytical methods developed by HPLC for the estimation of ursodeoxycholic acid in ursodeoxycholic acid tablets and capsules [9][10][11][12][13]. From the literature survey, it was observed that there is no stability indicating analytical method available for determination of drug quantity during stability studies.…”
Section: Introductionmentioning
confidence: 99%